Suzaku observations of the Monogem Ring and the origin of the Gemini H α ring. Issue 4 (12th April 2018) - Knies, Jonathan R; Sasaki, Manami; Plucinsky, Paul P
Abstract: We present the analysis of Suzaku X-ray observations of the Galactic supernova remnant (SNR) 'Monogem Ring', a large structure observed in X-rays with an extent of ≈25°, located at an anticentre position. One observation close to the shock also coincides with a large ring-like structure observed in H α, which is called the 'Gemini H α ring'. We investigate the origin of the ring-like structure and also possible interactions with the SNR. We show that the SNR is expanding in a region with a density gradient, which has an effect on the morphology of the SNR and the properties of the plasma. The X-ray spectra fit well with a collisional ionization equilibrium model with a temperature of kT ≈ 0.3 keV. The spectra obtained at a position where the SNR coincides with the Gemini H α ring are better described with non-equilibrium ionization with a temperature of kT ≈ 1.0 keV. Based on the spectral analysis results, we estimate an age of t ≈ 6.8 × 10 4  yr for a distance of ≈300 pc, using the Sedov–Taylor solution. We have identified several early-type stars in the Hipparcos catalogue at a distance of 200–300 pc, which have most likely formed the 'Gemini H α ring' by their powerful stellar winds.